DENOTATIVE AND CONNOTATIVE MEANING ANALYSIS IN THE GREATEST SHOWMAN ALBUM - Hadi, Irfan (Bahasa Indonesia Prima, 2021)
Tujuan dari penelitian ini adalah untuk menganalisis makna denotatif dan makna konotatif yang terkandung dalam lirik lagu pada album The Greatest Showman. Penelitian ini menggunakan analisis kualitatif deskriptif sebagai prosedur untuk melakukan penelitian. Penulis menemukan 27 lirik yang mengandung makna denotatif dan makna konotatif dalam sembilan lagu pada album The Greatest Showman. Hasil penelitian menunjukkan bahwa kata, frasa, atau kalimat dalam lirik lagu dalam album The Greatest Showman mengandung makna denotatif dan konotatif. Makna denotatif menunjukkan makna “kamus”. Makna konotatif menunjukkan makna tersirat yang mana menginterpretasikan berdasarkan konteks dalam semua lirik dalam lagu tersebut. Pesan umum dari seluruh lagu The Greatest Showman adalah memberi toleransi dan pantang menyerah untuk mencapai impian kita, menjadi diri kita sendiri, tidak takut untuk menjadi berbeda dan tidak peduli yang orang lain pikirkan atas impian kita Kata kunci : Denotasi, konotasi, analisis, snowman album Abstract-The purpose of this research is to analyze of the denotative and connotative meaning that are contained in the song lyrics of the greatest showman album this study uses descriptive qualitative analysis as a procedure for conducting research. The writer finds 10 lyrics that contain the denotative and connotative meaning in the nine songs of the greatest showman album. The results show that the word, phrases or sentences in the lyric song of the greatest showman album included denotative and connotative meaning. The denotative meaning shows the “dictionary” meaning. The connotative meaning shows the implied meaning that is interpreted based on the context of all lyrics in the songs. The general messages from the whole of the songs in the greatest showman are giving tolerance, not giving up on our dream, being ourself, not being afraid to be different, and not caring what others think of our dream. Key Words : Denotation, connotation, analysis, snowman album